The impact of supply and demand drivers on the iron ore price and cycle - Nortje, Petrus Gerhardus (My University, 2018)
Iron ore prices rallied from USD15/DMT during 2004 and experienced a significant drop from USD 140/DMT during the latter part of 2013. The purpose of the work is to identify the key drivers impacting on iron ore demand globally. Understanding the supply and demand balance and impact on price, is key to informed decision making relating to the iron ore business. The research methodology applied largely followed a quantitative methodology. Key drivers of iron ore demand, supply and demand balance and the impact on price were evaluated. The method applied consisted of gathering data from secondary sources and a detailed quantitative analysis on GDP, stage of economic development, steel consumption, supply and demand of iron ore and intensity of use. Approximately 98% of all iron ore is used for steel making and on that basis steel consumption is the primary driver for iron ore demand. Steel is mostly used for construction and manufacturing and is driven by emerging economies of which China is currently the largest contributor. Global GDP growth correlates well with steel consumption and is primarily driven by emerging economies. Urbanisation was and still is a key driver for construction in China, to provide housing and related infrastructure for transportation and services. Scrap steel recycling, currently at 15%, affect the demand for new steel and indirectly iron ore. Iron ore is abundant and can easily meet the demand. The significant growth from 2004/5 to 2013/14 and the unprecedented demand for steel resulted in elevated iron ore prices, introducing high cost iron ore, predominantly from Chinese State owned companies. From late 2013, the iron ore prices reduced significantly. This was mainly due to the steel consumption in China slowing down; delivering of large scale, low cost iron ore projects in Australia and Brazil and a significant reduction in oil prices. The key drivers impacting iron ore demand is: global GDP growth, industrialisation and urbanisation of emerging economies, recycling of steel, supply and demand balance of iron ore, the cost of production and the price of global iron ore. For the medium term outlook, the iron ore market will be structurally over-supplied and, as a result, the demand could be met at significantly lower cost of production levels than that seen during the period leading up to the price collapse in 2013. This is primarily because of the increase in low-cost supply from the major suppliers displacing higher cost producers. China will continue to grow and drive the global demand for steel and iron ore during the medium term albeit at much lower rates when compared to the last decade. The demand for steel will increase until 2020 according to various analyst views. The iron ore prices are expected to trade between USD50/DMT to USD70/DMT from 2016 to 2020 mainly because of the over-supply situation and demand being mostly met by large scale, low-cost producers. The decision around the continuation of high cost, state owned Chinese iron ore producers, new large-scale low cost production and the oil price will impact on the price outlook.
Thesis is submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Mining Engineering, University of the Witwatersrand, Johannesburg, 2018
Keywords: Iron ores; Mines and mineral resources